Utilization of the halophytic shrubs Atriplex nummularia Lindl and Rhagodia preissii Moq as crops in salt-affected semi-arid regions: How temperature, salinity, seed weight and size affect seed germination - Christiansen, Aslak H. C.; Norman, Hayley C.; Andreasen, Christian (Frontiers in Plant Science, 2022)
The perennial halophytic shrubs Atriplex nummularia and Rhagodia preissii are native to Western Australia and can be planted on saline land to produce animal feed during the autumn. However, an impediment to the adoption of the species on saline land has been the challenges in achieving successful establishment by direct seeding due to a lack of knowledge of the optimal conditions for germination. Therefore, the optimal germination requirements in relation to temperature, salinity level and seed size was assessed for each species to ascertain the optimal conditions for successful establishment by direct seeding on saline land. Seeds of both species showed optimal germination temperature at 10 °C. Atriplex nummularia seeds were more tolerant to temperatures above or below 10 °C than R. preissii. The germination percentage of A. nummularia was unchanged at 0–200 mM NaCl2. The germination percentage of Rhagonia preissii declined when the NaCl2 content exceeded 50 mM. There was no correlation between seed size, germination and emergence for any of the species. Based on the study, we suggest that sowing operations are performed during the cold winter months in subtropical areas to improve the successful establishment of these shrubs by direct seeding.